2020
DOI: 10.3390/ijerph17218105
|View full text |Cite
|
Sign up to set email alerts
|

Solar UV Radiation in the Tropics: Human Exposure at Reunion Island (21° S, 55° E) during Summer Outdoor Activities

Abstract: Reunion Island is a popular tourist destination with sandy beaches, an active volcano (Piton de la Fournaise), and Piton des Neiges, the highest and most dominant geological feature on the island. Reunion is known to have high levels of solar ultraviolet radiation (UVR) with an ultraviolet index (UVI) which can reach 8 in winter and 16 in summer (climatological conditions). UVR has been linked to skin cancer, melanoma, and eye disease such as cataracts. The World Health Organization (WHO) devised the UVI as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Cumulated over the day, we found that the health risk thresholds were exceeded from 09:00 in the morning for phototype I skin and from 11:00 for phototype VI skin and, over the whole day, the maximum accumulation was 60 J·m −2 on Karthala and 50 J·m −2 at Moroni. These SED and cumulative SED values (over 50 SED) are close to those obtained in this region of the globe at similar latitudes by [ 13 ]. In the northern hemisphere, in Spain, cumulative SED values of over 60 SED were also reported by [ 55 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Cumulated over the day, we found that the health risk thresholds were exceeded from 09:00 in the morning for phototype I skin and from 11:00 for phototype VI skin and, over the whole day, the maximum accumulation was 60 J·m −2 on Karthala and 50 J·m −2 at Moroni. These SED and cumulative SED values (over 50 SED) are close to those obtained in this region of the globe at similar latitudes by [ 13 ]. In the northern hemisphere, in Spain, cumulative SED values of over 60 SED were also reported by [ 55 ].…”
Section: Discussionsupporting
confidence: 89%
“…The same Solarmeter 6.5 instrument was successfully used in previous works and similar situations [ 10 , 12 ]. Furthermore, as reported by [ 13 ], the Solarmeter instrument was regularly calibrated during side-by-side intercomparison campaigns with the Bentham DTMc spectrophotometer and shows a small discrepancy, with an overestimation of about 12%. For each UVI measurement with the Solarmeter, environmental observations were also made.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Several other studies have focused on determining the UV exposure doses received during specific activities like cycling, jogging and hiking ( 16 , 17 , 29 34 ). They differ mainly in the selection of the participant collective, the measurement technology used, the duration of the measurement, and the selection of the activities studied.…”
Section: Introductionmentioning
confidence: 99%
“…Solar Ultraviolet Radiation (UVR) comprises a set of electromagnetic waves with wavelengths between 100 and 400 nm that represents a small fraction (5%) of the solar radiation that reaches the terrestrial surface [1][2][3]. This spectrum of solar radiation has a direct effect on human health, terrestrial and aquatic ecosystems, and the degradation of materials [4,5].…”
Section: Introductionmentioning
confidence: 99%